2020
DOI: 10.1002/acn3.51269
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter imaging predicts clinically‐defined α‐synucleinopathy in REM sleep behavior disorder

Abstract: IntroductionIndividuals with idiopathic rapid eye movement sleep behavior disorder (iRBD) are at high risk for a clinical diagnosis of an α‐synucleinopathy (aSN). They could serve as a key population for disease‐modifying trials. Abnormal dopamine transporter (DAT) imaging is a strong candidate biomarker for risk of aSN diagnosis in iRBD. Our primary objective was to identify a quantitative measure of DAT imaging that predicts diagnosis of clinically‐defined aSN in iRBD.MethodsThe sample included individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…The single parameter "pathological [ 123 I]FP-CIT-SPECT" provided an annual CR in all, i.e., RBD and iRBD patients of ∼10% and identified all phenoconverters. To select iRBD patients in the late prodromal stage, i.e., with an already affected dopaminergic nigrostriatal pathway, [ 123 I]FP-CIT-SPECT appears to be the best single parameter, which is in agreement with earlier studies [29,30]. However, it fails to detect iRBD patients at risk with a still intact nigrostriatal pathway, i.e., who are in the prodromal "prenigral" stage.…”
Section: Discussionsupporting
confidence: 75%
“…The single parameter "pathological [ 123 I]FP-CIT-SPECT" provided an annual CR in all, i.e., RBD and iRBD patients of ∼10% and identified all phenoconverters. To select iRBD patients in the late prodromal stage, i.e., with an already affected dopaminergic nigrostriatal pathway, [ 123 I]FP-CIT-SPECT appears to be the best single parameter, which is in agreement with earlier studies [29,30]. However, it fails to detect iRBD patients at risk with a still intact nigrostriatal pathway, i.e., who are in the prodromal "prenigral" stage.…”
Section: Discussionsupporting
confidence: 75%
“… 17 Moreover, several single‐center studies found that presynaptic dopaminergic imaging is a good predictor of subsequent phenoconversion of iRBD patients. 18 , 19 , 20 , 21 Finally, a recent international multicenter study, found that nigroputaminal dopaminergic impairment, as investigated by 123 I‐FP‐CIT‐SPECT, is the strongest predictor of phenoconversion in iRBD. 2 Therefore, 123 I‐FP‐CIT‐SPECT is likely going to be used as an enrichment biomarker in upcoming clinical trials in prodromal synucleinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, iRBD patients often have nigrostriatal dopaminergic impairment 17 . Moreover, several single‐center studies found that presynaptic dopaminergic imaging is a good predictor of subsequent phenoconversion of iRBD patients 18‐21 . Finally, a recent international multicenter study, found that nigroputaminal dopaminergic impairment, as investigated by 123 I‐FP‐CIT‐SPECT, is the strongest predictor of phenoconversion in iRBD 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a progressive decline in striatal binding in patients with iRBD further support the notion that RBD is actually an integral prodromal period of a defined neurodegenerative syndrome [ 182 ]. Several recent studies confirmed the high sensitivity of abnormal DAT-SPECT to accurately predict the short-term conversion to a clinically-defined α-synucleinopathy [ 183 , 184 , 185 , 186 , 187 ].…”
Section: Dat Imaging As Preclinical Biomarkermentioning
confidence: 88%